Future restoration should enhance ecological complexity and emergent properties at multiple scales. Issue 4 (7th December 2021) - Bullock, James M.; Fuentes‐Montemayor, Elisa; McCarthy, Ben; Park, Kirsty; Hails, Rosie S.; Woodcock, Ben A.; Watts, Kevin; Corstanje, Ron; Harris, Jim
Abstract : Ecological restoration has a paradigm of re‐establishing 'indigenous reference' communities. One resulting concern is that focussing on target communities may not necessarily create systems which function at a high level or are resilient in the face of ongoing global change. Ecological complexity – defined here, based on theory, as the number of components in a system and the number of connections among them – provides a complementary aim, which can be measured directly and has several advantages. Ecological complexity encompasses key ecosystem variables including structural heterogeneity, trophic interactions and functional diversity. Ecological complexity can also be assessed at the landscape scale, with metrics including β diversity, heterogeneity among habitat patches and connectivity. Thus, complexity applies, and can be measured, at multiple scales. Importantly, complexity is linked to system emergent properties, e.g. ecosystem functions and resilience, and there is evidence that both are enhanced by complexity. We suggest that restoration ecology should consider a new paradigm to restore complexity at multiple scales, in particular of individual ecosystems and across landscapes. A complexity approach can make use of certain current restoration methods but also encompass newer concepts such as rewilding. Indeed, a complexity goal might in many cases best be achieved by interventionist restoration methods. Incorporating complexity into restoration policies could be quite straightforward. Related aims such as enhancing ecosystem services and ecological resilience are to the fore in initiatives such as the Sustainable Development Goals and the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services. Implementation in policy and practice will need the development of complexity metrics that can be applied at both local and regional scales. Ultimately, the adoption of an ecological complexity paradigm will be based on an acceptance that the ongoing and unprecedented global environmental change requires new ways of doing restoration that is fit for the future.